Earnings inequality and market work in husband-wife families - John H. Pencavel (Institute for the Study of Labor (IZA), 2006)
Constructing pseudo-panel data from successive Current Population Surveys, this paper analyzes earnings inequality in husband and wife families over the life cycle and over time. Particular attention is devoted to the role of labor supply in influencing measures of earnings inequality. Compact and accurate descriptions of earnings inequality are derived that facilitate the analysis of the effect of the changing market employment of wives on earnings inequality. The growing propensity of married women to work for pay has mitigated the increase in family earnings inequality. Alternative measures of earnings inequality covering people with different degrees of attachment to the labor market are constructed. Inferences about the extent and changes in earnings inequality are sensitive to alternative labor supply definitions especially in the case of wives.
Keywords: J31; J22; D63; 330; earnings inequality; married women's employment-population ratios; hours of work; Haushaltsökonomik; Haushaltseinkommen; Einkommensverteilung; Frauenerwerbstätigkeit; Theorie